2021
DOI: 10.1021/acs.jpcb.1c05369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Phase Equilibria and Transport Properties in a Model CO2-Expanded Lithium Perchlorate Electrolyte

Abstract: Carbon-dioxide (CO2)-expanded liquids, in which a significant mole fraction of CO2 is dissolved into an organic solvent, have been of significant interest, especially as catalytic support media. Because the CO2 mole fraction and density can be controlled over a significant range by changing the CO2 partial pressure, the transport properties of these solvents are highly tunable. Recently, these liquids have garnered interest as potential electrolyte solutions for catalytic electrochemistry; however, little is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We have recently used this approach to examine many dynamical and equilibrium properties of water (and other systems ) including OH reorientation and self-diffusion. ,,, One can use these results to carry out a simple thought experiment. If OH reorientation and diffusion (and other dynamics) in water is controlled by H-bond exchanges, the jump time should be the single characteristic of all of these dynamics.…”
Section: The Central Role Of Activation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently used this approach to examine many dynamical and equilibrium properties of water (and other systems ) including OH reorientation and self-diffusion. ,,, One can use these results to carry out a simple thought experiment. If OH reorientation and diffusion (and other dynamics) in water is controlled by H-bond exchanges, the jump time should be the single characteristic of all of these dynamics.…”
Section: The Central Role Of Activation Energiesmentioning
confidence: 99%
“…For example, the detailed insight into activation energies offered by the fluctuation theory for dynamics should enable greater consideration of dynamical properties in the development of force fields for molecular simulations. Moreover, while the focus here is on liquid water, corresponding examinations of activation energies and volumes for dynamics in nonaqueous liquids, electrolyte solutions, , nanostructured materials, and biological systems, will present new challenges but also yield improved mechanistic descriptions.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Piskulich and Laird also calculated the diffusion activation energy for MeCN and CO 2 using fluctuation theory methods for a CXE system with MeCN solvent and lithium perchlorate electrolyte. 17 kJ/mol. These results use the same MeCN model and again show excellent agreement with our results, while the minor differences may be attributed to the differences in electrolyte identity and system composition at the different pressures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Piskulich and Laird conducted molecular dynamics (MD) simulations on an acetonitrile (MeCN)-based CXE with lithium perchlorate salt to assess the impact of electrolyte concentration on CO 2 expansion and transport properties of the CXE. 17 In our recent work, we combined experimental and theoretical approaches to quantify solution conductivity with CO 2 expansion, addressing a crucial limitation of CXEs: as more nonpolar CO 2 molecules are added, the solution conductivity diminishes. 8 We obtained excellent agreement between the experimentally measured solution conductivity and values obtained from MD simulations for a MeCN-based CXE with a tetraalkylammonium hexafluorophosphate electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…They found that increased tensile strain causes the binding strength of *COOH and *CHO to increase but causes the binding strength of *CO and *COH to decrease. Piskulich and Laird used classical molecular dynamics and Monte Carlo simulations to study a model of CO 2 -expanded acetonitrile electrolyte containing lithium perchlorate . This class of electrolytes has a high solvent conductivity while also having a high solubility for CO 2 , which is crucial for the efficient reduction of CO 2 to CO. Their calculations show that diffusion increases for all species with increasing CO 2 concentration but decreases significantly with the addition of the electrolyte.…”
mentioning
confidence: 99%